Optimasi Jaringan Wi-Fi Menggunakan Metode Analisis Quality Of Service Berdasarkan Thipon - Ahmad Akbar Resa; Dewi Handayani UN (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
QoS (Quality of Service) on the internet network at STIKUBANK University Semarang should be maintained optimally as one of the efforts to meet the needs of internet users on campus. The purpose of this research was to determine the quality and service of the Wifi network in Building D8, STIKUBANK University Semarang so that it can determine the level of satisfaction of the users of the wifi network and minimize network disruptions early on so that the internet network is always at its best.. The QoS (Quality of Service) parameters used in this study are bandwidth, delay, packet loss and jitter based on the TIPON standard by monitoring the internet network at the Access Point of each room using the Axence NetTools application. Some of these rooms include: WR Room, YPPMI Room, TU Room, Meeting Room, Rector Room and HR Room. This research has benefits both theoretically and practically. Theoretically, the benefit of this research is that it can be a reference for other researchers who will discuss QoS (Quality of Service) analysis of Wifi networks at schools, colleges or other institutions. And practically, the results of this study can be used as material for study and information for STIKUBANK University Semarang regarding the QoS (Quality of Service) of the Wifi network in Building D8, STIKUBANK University Semarang. Based on the results of the research that has been done, it can be concluded that the QoS (Quality of Service) of the Wifi network in Building D8 of Stikubank University (UNISBANK) according to the TIPON standard is satisfactory with a percentage of 91.67% and is included in the grade B category. Keyword : QoS (Quality of Service), Wi-Fi, TIPHON, Axence NetTools.